Challenges and Solutions of Philosophy in Islamic Studies in the Contemporary Era - Rizki, Aulia; Ulfa, Maria; Nazarullah, Nazarullah (Desultanah: Journal Education and Social Science, 2025)
This study examines the role of Islamic philosophy in addressing contemporary challenges faced by Muslim societies, particularly in relation to secularism, Western rationalism, globalization, and technological development. Although Islamic philosophy has a rich intellectual legacy in theology and metaphysics, its application to modern issues still faces inconsistencies, especially in integrating Islamic values with social realities and scientific progress. This research employs a qualitative approach through library research, with data analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that Islamic philosophy has great potential to serve as an instrument of reform in Islamic education by developing methodologies relevant to modern issues and integrating ethical principles with scientific and technological advancements. This article argues that the revitalization of Islamic philosophy is necessary to ensure its adaptability to global challenges without neglecting the fundamental principles of Islam. Thus, this study enriches the academic discourse by providing a deeper understanding of the contribution of Islamic philosophy in integrating spiritual values with the demands of modern life.